2018
DOI: 10.1088/1748-9326/aae492
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of heterogeneous HONO formation from aerosols and the regional photochemical impact of this HONO source

Abstract: Large missing daytime HONO sources have been reported by many previous studies around the world. Possible HONO sources include ground heterogeneous conversion, aerosol heterogeneous formation, soil emission, and photochemical production. In this study, a consistent 1D framework based on regional and 3D chemical transport models (CTMs) was used to analyze the unknown daytime HONO sources in 14 cases worldwide. We assume that the source of HONO from aerosols is through NO 2 hydrolysis (not including its oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 58 publications
2
38
0
Order By: Relevance
“…The abundance of other gaseous acids and bases affected the efficiency of HONO collection by AIM due to the relationship between Henry's law constant and pH. This measurement method and its details have been successfully evaluated in many field studies (Markovic et al, 2012;Wang et al, 2019;Yang et al, 2020), as shown in the Supplement. In addition, a QXZ1.0 automatic weather station (Yigu Technologies, China) was used for the synchronous observation of meteorological parameters, including temperature (T ), RH, wind direction (WD), and wind speed (WS).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of other gaseous acids and bases affected the efficiency of HONO collection by AIM due to the relationship between Henry's law constant and pH. This measurement method and its details have been successfully evaluated in many field studies (Markovic et al, 2012;Wang et al, 2019;Yang et al, 2020), as shown in the Supplement. In addition, a QXZ1.0 automatic weather station (Yigu Technologies, China) was used for the synchronous observation of meteorological parameters, including temperature (T ), RH, wind direction (WD), and wind speed (WS).…”
Section: Instrumentsmentioning
confidence: 99%
“…The present analysis simplified this process by treating the ground and aerosol surfaces in the same way. The uptake co-efficient is mainly dependent on the surface characteristics, e.g., surface type and moisture (Lu et al, 2018).…”
Section: Heterogeneous Conversion Of No 2 To Honomentioning
confidence: 99%
“…(1). However, the field observations in the last decade have indicated that the [HONO] PSS can only account for a small portion of the measured concentrations in a variety of environments (Kleffmann et al, 2005;Zhou et al, 2007;Michoud et al, 2014), suggesting the action of additional daytime HONO sources. To explain the observed HONO levels, some new formation mechanisms have been proposed and tested in the lab or through field studies (Bejan et al, 2006;Monge et al, 2010;Su et al, 2011;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…HONO in both clean and haze periods shows a distinct diel pattern, with a large decrease in the morning from loss through photolysis and a minimum in the afternoon; a large increase in HONO concentration overnight probably originates from heterogeneous sources (i.e. NO2 converting to 305 HONO on humid surfaces) (Finlayson-Pitts et al, 2003;Lee et al, 2015;Li et al, 2012;Lu et al, 2018;Zhang et al, 2016b;Zhou et al, 2003). The HONO concentration was a factor of 3 higher on average during haze periods at midday than during the clearer periods.…”
Section: Chemical and Meteorological Conditionsmentioning
confidence: 97%